Foremost Disciples: Ideal Leaders in Buddhism - ฐิตกุสโล, พระครูวิจิตรปริยัตยากร; นันทเพ็ชร, กฤษฎา (Journal of Educational Review Faculty of Education in MCU, 2018)
This article is focused on leadership of the foremost disciples in Buddhism in of the 21st centuryframeworkemphasizing the skills of executives with good and intellectual quality and ability in leading the organizations to a happy workplace based on Buddhist principles from 80 foremost disciples. The qualifications obtained from those disciples can develop emotional quotient of leaders to manage man with kindness and hospitality, good at work, intellectual, able to mage man and work system, to be a model in work of co-workers and subordinates, and arrange environment suitable to workbased on Buddhist principles according educational framework in the 21st century.